2
$\begingroup$

In an A level C2 textbook I have found a question:

$\log_2 x +\log_4 x = 2$

From attempting the question, I suspect I may need to try and inverse the logarithm, and on testing, I found that e to the power of ... looked promising but I am not sure. And my knowledge of logarithms is very limited.

Can anyone solve this and explain the answer, and also, because I think it is closely linked to the question, why is e useful and why is it 2.7... ?

$\endgroup$
1
  • $\begingroup$ You can use the change-of-base formula and write $2 = \log_2x + \log_4x = \log_2 x + \log_2x/\log_24 = \log_2x + \frac12\log_2x = \frac32 \log_2x$. Now take it from here. $\endgroup$
    – user217285
    Feb 24, 2017 at 13:01

6 Answers 6

2
$\begingroup$

$$\log_2 x +\log_4 x = 2$$ $$\frac{1}{\log_ x2} +\frac{1}{\log_ x4} = 2$$ $$\frac{1}{\log_ x2} +\frac{1}{2\log_ x2} = 2$$ $$\frac{3}{2\log_ x2} = 2$$ $$\frac{1}{\log_ x2} =\frac{4}{3}$$ $$\log_ 2x =\frac{4}{3}$$ $$x=2^{4/3}$$

$\endgroup$
3
  • $\begingroup$ Could you explain the last step? $\endgroup$
    – Melkor
    Feb 24, 2017 at 12:54
  • 1
    $\begingroup$ @Melkor it is the definition of the logarithm. $\endgroup$ Feb 24, 2017 at 13:01
  • $\begingroup$ Sorry I misread as a mixed fraction and got confused... $\endgroup$
    – Melkor
    Feb 24, 2017 at 13:06
1
$\begingroup$

we write $$\frac{\ln(x)}{\ln(2)}+\frac{\ln(x)}{2\ln(2)}=2$$ multiplying by $$2\ln(2)$$ we obtain $$2\ln(x)+\ln(x)=4\ln(2)$$thus we get $$\ln(x)=\frac{4}{3}\ln(2)$$ can you finish this?

$\endgroup$
1
$\begingroup$

If we apply 4^ to both sides, we get

$$4^{\log_2(x)+\log_4(x)}=16$$

$$4^{\log_2(x)}4^{\log_4(x)}=16$$

Since $4=2^2$, this reduces to

$$2^{2\log_2(x)}4^{\log_4(x)}=16$$

$$x^2\cdot x=16$$

$$x^3=16$$

$$x=\sqrt[3]{16}\approx2.7$$

$\endgroup$
2
  • $\begingroup$ Could you explain how you got to $x^2 * x =16$ ? $\endgroup$
    – Melkor
    Feb 24, 2017 at 12:57
  • 1
    $\begingroup$ Note the logarithms cancel by definition, since: $$4^{\log_4(x)}=x$$and$$2^{2\log_2(x)}=(2^{\log_2(x)})^2=x^2$$ $\endgroup$ Feb 24, 2017 at 13:00
0
$\begingroup$

You would need to change the base of one of the $log$. For example $\log_4 x = \frac{\log_2 x}{log_2 4} = \frac{\log_2 x}{2}$ $$ 2 = \log_2 x + \log_4 x = \frac{3}{2} \log_2x \implies x = 2^{4/3} = \sqrt[3]{16} $$

$\endgroup$
0
$\begingroup$

Use the definition of $\log_a x=\ln(x)/\ln(a)$ and multiply $\log_2 x + \log_4 x = 2$ by $2 \ln 2$ to get $3\ln x=2$, hence $x=\exp(2/3)$.

$\endgroup$
0
$\begingroup$

Here is another way to think. First note that $4$ is a power of $2$

Let $\log_4x=k\iff 4^k=x$

Now $4^k=x \implies (2^2)^k=x \implies 2^{2k}=x\iff\log_2x=2k\implies \frac{1}{2}\log_2{x}=\log_4{x}$

We now have $$\log_2x+\frac{1}{2}\log_2x=2\\\frac{3}{2}\log_2x=2\\\log_2x^{3/2}=2\iff2^2=x^{3/2}\implies x=16^{1/3}$$

I added this because it reinforces the bonds between logs and powers.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.